The Essence and Principles of Combating Corruption in the Field of Public Procurement - KATAYEV, Nurbek A.; MOLDABAEV, Sarkytbek S.; BEGALIYEV, Bakhytbek A.; AUBAKIROVA, Anna A.; BEGALIYEV, Yernar N. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).12, 2019)
Around the world, the process of globalization, including economic processes, is proceeding rapidly. As a result, there was an opinion about the need to erase state borders, including in the field of public procurement. In the article, the author outlines the basic principles of combating corruption in public procurement. In particular, 7 basic principles are identified: efficiency; profitability; competitiveness; professionalism; equality and justice; transparency and publicity; responsibility. According to the author, these principles should be basic and fundamental in combating corruption in public procurement. With that, the advantages and disadvantages of existing models of public procurement management in the modern world are analyzed, according to the results of which, it was concluded that a centralized model of public procurement is the most effective for combating corruption.